[OP.1A.02] INNATE IMMUNITY AND CARDIO-RENAL RISK IN STAGE 2-5 CKD PATIENTS. (September 2017) - Zoccali, C.; Pizzini, P.; Leonardis, D.; Torino, C.; Postorino, M.; D'Arrigo, G.; Tripepi, G.; Mallamaci, F.
Abstract : Objective: The soluble form of urokinase-type plasminogen activator (suPAR) is a powerful marker for immune activation that accurately predict clinical outcomes in patients with sepsis or infectious diseases. Alterations in innate immunity and Inflammation are major risk factors for the high risk for cardiovascular disease in patients with chronic kidney disease (CKD) but whether suPAR predicts cardiovascular and renal complications independently of established risk factors in CKD is still unknown. Design and method: We measured plasma suPAR levels (ELISA) and a series of traditional and CKD-specific risk factors in 753 stage G2-5 CKD patients. We estimated the risk for GFR loss (>30%) or kidney failure, time to death and first cardiovascular event by multivariate Cox regression analysis adjusting for traditional risk factors and a large series of CKD-specific risk factors. Results: suPAR was gender-dependent and associated with lower GFR and higher proteinuria, older age, diabetes, higher systolic BP, C Reactive Protein (CRP), phosphate, PTH, FGF23, ADMA and lower Hb, 25OH vitD and 1, 25OH2 vitD (all P < 0.001). Over a 31 +/− 10 months follow-up 42 patients died and 95 had a renal event. suPAR was a strong predictor of the combined end-point death and cardiovascular events [HR (500pg/ml): 1.09, 95%CI: 1.04–1.14] in a Cox's regression analysis adjusting for a large series of potential confounders including background cardiovascular disease, the GFR, proteinuria, age, gender, smoking, diabetes, systolic BP and anti-hypertensive treatment, phosphate, Hb, serum albumin, BMI, CRP, ADMA and FGF23. Separate analyses of time to death and time to first CV event were both highly significant (P < 0.01) in crude and adjusted analyses. Conclusions: Elevated suPAR levels robustly predict incident cardiovascular events and death in CKD patients. These findings go along with biological knowledge documenting a strong role of suPAR in atherosclerosis and support the contention that suPAR is causally implicated in cardiovascular disease in CKD patients.